LAPORAN PELAKSANAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING YANG DIMODIFIKASI BERBASIS DIFERENSIASI DAN TPACK PADA MATERI RANTAI MAKANAN DAN JARING-JARING MAKANAN SISWA KELAS V - Pandi Fajar Kurniawan; Muhammad Amin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to describe the implementation of the Modified Problem Based Learning (PBL) Learning Model with the Differentiation and TPACK approaches in the Natural and Social Sciences (IPAS) subject in Grade V of SD Negeri 2 Bandar Sakti. The implementation procedure of this model includes five PBL syntaxes applied in 3 meetings, using process and product differentiation to serve learning styles (Visual, Audio Visual, Kinesthetic) and student learning readiness. The results of the implementation show that the application of this modified PBL Model has succeeded in significantly improving students' conceptual understanding of Food Chains and Food Webs, which is seen from the average increase in summative assessment scores of 15 points from the diagnostic assessment. In addition, the use of Role Play and Gallery Walk activities has proven very effective in motivating students and encouraging creativity in presenting their work. The conclusion of this report is that the modified PBL Model, which is integrated with differentiation and TPACK, is an innovative and interactive learning design that is effective in achieving learning objectives and developing students' 21st-century skills.